First reported Porrocaecum angusticolle infection in Griffon vulture (Gyps fulvus) in China - Liu, Gongzhen; Liu, Qing; Zhang, Wei; Shen, Xuewen (Frontiers in Cellular and Infection Microbiology, 2023)
This present study is the first case of a Porrocaecum angusticolle (P. angusticolle) infection reported in Griffon vulture (Gyps fulvus) in China. This study aimed to identify the nematode species and explore the genetic evolution of worms infecting Gyps fulvus (G.fulvus). Clinical examination revealed several milky white parasites in the stomach and intestinal tract. Polymerase chain reaction and partial 18S gene sequencing analyses identified these worms to be P. angusticolle (SD isolates). Further phylogenetic analyses revealed that they shared the highest genetic identity (99.9%) with a P. angusticolle isolate (EU004820.1) from Germany. Our study is the first report on the identification and characterization of P. angusticolle infecting G.fulvus in China, based on clinical findings and molecular diagnosis. Therefore, our study provides novel insights for the diagnosis of P. angusticolle infections and the prevention of nematode transmission in wild and domestic animals.